Ions Transport and Adsorption Mechanisms in Porous Electrodes During Capacitive-Mixing Double Layer Expansion (CDLE) - Rica, Raúl A. (American Chemical Society, 2012)
[Image: see text] A model of the electro-diffusion of ions in porous electrodes is applied to analyze the dynamics of capacitive-mixing extraction of energy from salinity gradients with carbon porous electrodes. The complex time-evolution of the cell voltage observed in experiments is satisfactorily described. The asymmetry on the duration of the solution-change steps performed in open circuit is found to be due to the nonlinear voltage–concentration relationship of the electric double layers and to a current that redistributes the counterions along the depth of the electrode leading to nonuniform charge and salt adsorption. The validated model is an essential tool for the design and optimization of renewable energy extraction by this technique.